Assessing the Relationship between Atherosclerotic Cardiovascular Disease Risk Score and Carotid Artery Imaging Findings. Issue 1 (25th October 2018) - Li, Ying; Zhu, Guangming; Ding, Victoria; Huang, Yonghua; Jiang, Bin; Ball, Robyn L.; Rodriguez, Fatima; Fleischmann, Dominik; Desai, Manisha; Saloner, David; Saba, Luca; Hom, Jason; et al.
ABSTRACT: BACKGROUND AND PURPOSE: To characterize the relationship between computed tomography angiography (CTA) imaging characteristics of carotid artery and the 10‐year risk of atherosclerotic cardiovascular disease (ASCVD) score. METHODS: We retrospectively identified all patients who underwent a cervical CTA at our institution from January 2013 to July 2016, extracted clinical information, and calculated the 10‐year ASCVD score using the Pooled Cohort Equations from the 2013 ACC/AHA guidelines. We compared the imaging features of artery atherosclerosis derived from the CTAs between low and high risk. RESULTS: One hundred forty‐six patients met our inclusion criteria. Patients with an ASCVD score ≥7.5% (64.4%) had significantly more arterial stenosis than patients with an ASCVD score <7.5% (35.6%, P < .001). Maximal plaque thickness was significantly higher (mean 2.33 vs. .42 mm, P < .001) and soft plaques (55.3% vs. 13.5%, P < .001) were significantly more frequent in patients with an ASCVD score ≥7.5%. However, among patients with a 10‐year ASCVD score ≥7.5%, 33 (35.1%) had no arterial stenosis, 35 (37.2%) had a maximal plaque thickness less than. 9 mm, and 42 (44.7%) had no soft plaque. Furthermore, among the patients with a 10‐year ASCVD score <7.5%, 8 (15.4%) had some arterial stenosis, 8 (15.4%) had a maximal plaque thickness more than. 9 mm, and 7 (13.5%) had soft plaque. CONCLUSION: There is some concordance but not a perfect overlap between the 10‐year ASCVD risk scores calculated from clinical and blood assessment and carotid artery imaging findings.